2005
DOI: 10.1111/j.0022-202x.2004.23548.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sun Exposure in Determining Nevus Density in UK Adolescent Twins

Abstract: We report a study of 221 teenage twin pairs to examine the genetic and environmental determinants of nevi representing the most potent phenotypic risk factor for melanoma. Our published heritability analysis estimated that nevi are mainly genetically determined. In this paper we examine the role of sun exposure. We report a correlation between nevus density and sun exposure, particularly that acquired in hotter countries than in the UK (mean nevus density 41 per m2 in those in the highest quartile of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…Bauer et al found that German children who wore the most number of clothes at the beach or pool had whole-body nevus counts 24% lower than those who wore the fewest clothes (7). In contrast, a third study of twins in the United Kingdom found no association between nevi on the trunk and wearing shirts while on the beach during a ''hot holiday'' (13).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Bauer et al found that German children who wore the most number of clothes at the beach or pool had whole-body nevus counts 24% lower than those who wore the fewest clothes (7). In contrast, a third study of twins in the United Kingdom found no association between nevi on the trunk and wearing shirts while on the beach during a ''hot holiday'' (13).…”
Section: Discussionmentioning
confidence: 85%
“…Australia, with generally high UV radiation, has much higher incidence of melanoma than the United Kingdom, with generally low levels, and children in Australia have more nevi than children in the United Kingdom (14)(15)(16). Two European studies found that wearing clothing during vacations was associated with fewer nevi (7,12), whereas a third found no association (13). In a study of 6-to 7-year-old children, exposure was measured during vacations away from home (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] An alternative hypothesis was that sunscreen use could encourage sun exposures of longer duration, possibly leading to increased risk of melanoma and of BCC. In this article, we review observational and randomized studies that examined sunscreen use and sun exposure duration, according to the sun exposure type associated with sunscreen use.…”
mentioning
confidence: 99%
“…Some patients present with few lesions, while others have hundreds. Melanocytic naevi develop through childhood and twin studies provide good evidence that naevus number is predominantly genetically determined [3] with a smaller effect of sun exposure [4]. Melanocytic naevi can be broadly divided into congenital and acquired types.…”
Section: Discussionmentioning
confidence: 99%